The Effect of Human Resource Management and Work Discipline on Employee Performance with Work Motivation as a Mediation Variable in a Property Consulting Company in Ubud Gianyar - Putu Asri Anggita Putri (Business Management, 2025)
The phenomenon of low employee motivation and discipline, which leads to decreased productivity, poses a real challenge for many companies, including those in the property sector. Although various human resource management (HRM) policies have been implemented, the results have not been entirely effective in improving employee performance. This study aims to analyze the influence of human resource management and work discipline on employee performance, with work motivation as a mediating variable at a Property Consulting company in Ubud, Gianyar. A quantitative approach was used in this research with data analysis techniques employing Partial Least Squares (PLS). The number of respondents was 38 employees selected using a census method. The results indicate that HRM has a positive and significant effect on employee performance, both directly and through work motivation as a mediating variable. Work discipline also shows a positive effect on employee performance, with work motivation acting as a mediator that strengthens this relationship. In addition, HRM and work discipline have a significant influence on work motivation. This study concludes that effective HRM strategies and discipline can enhance both motivation and employee performance. The practical implication of this research is the need to improve the quality of HR management and to create a work system that is both disciplined and motivating.